Inter-Individual Different Responses to Continuous and Interval Training in Recreational Middle-Aged Women Runners - Bonet, Jèssica B.; Magalhães, José; Viscor, Ginés; Pagès, Teresa; Ventura, Josep L.; Torrella, Joan R.; Javierre, Casimiro (Frontiers in Physiology, 2020)
A crucial subject in sports is identifying the inter-individual variation in response to training, which would allow creating individualised pre-training schedules, improving runner’s performance. We aimed to analyse heterogeneity in individual responses to two half-marathon training programmes differing in running volume and intensity in middle-aged recreational women. Twenty women (40±7 years, 61±7kg, 167±6cm, VO2max=48±6 mL·kg-1·min-1) underwent either moderate-intensity continuous (MICT) or high-intensity interval (HIIT) 12-week training. They were evaluated before and after training with maximal incremental tests in the laboratory (VO2max) and in the field (time to exhaustion, TTE; short interval series and long run). All the women participated in the same half-marathon and their finishing times were compared with their previous times. Although the improvements in the mean finishing times were not significant, MICT elicited a greater reduction (3min 50s, P=0.298), with more women (70%) improving on their previous times, than HIIT (reduction of 2min 34s, P=0.197, 50% responders). Laboratory tests showed more differences in the HIIT group (P=0.008), while both groups presented homogeneous significant (P<0.05) increases in TTE. Both in the short interval series and in the long run, HIIT induced better individual improvements, with a greater percentage of responders compared to MICT (100% versus 50% in the short series and 78% versus 38% in the long run). In conclusion, variability in inter-individual responses was observed after both MICT and HIIT, with some participants showing improvements (responders) while others did not (non-responders) in different performance parameters, reinforcing the idea that individualised training prescription is needed to optimise performance.